Fault Tolerant Control in Z-Source Inverter Fed Induction Motor - B. Justus Rabi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2011)
This paper discusses about the detection and replacement of the switches in inverter under fault. The detection of switch is done through measuring the phase and line voltages of inverter. The replacement of the open switch is done through the extra arm provided in the circuit. The firing of the extra arm is done by detecting the open switch fault and interrupting the processor to provide the firing to the extra arm switch. This paper gives simple and effective detection and replacement of open switch. The replacement of switch will be done without stopping the whole system and saves the unspecified time. Simulation results are provided to demonstrate the detection and replacement. A feasible test is implemented by building a proto type three-phase impedance source inverter, which is designed and controlled on the basis of proposed considerations. It is verified from the practical point of view that this new approach is more effective and acceptable to minimize the distortion. Keywords: SMPS – Switch Mode Power Supply, pulse width modulation (PWM), VSI –Voltage Source Inverter.DOI: http://dx.doi.org/10.11591/ijpeds.v1i1.67